Effects of particle size and mixing time on uniformity and segregation in pig diets - Amornthewaphat, N.; Behnke, Keith C.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Diet uniformity, as represented by the coefficient of variation (CV), improved as mixing time was increased from 15 to 120 seconds and(or) com particle size was decreased from 1,200 to 400 ~m. Segregation occurred during free-fall, and the coarser particle sizes resulted in greater segregation than the finer particle sizes. Thus, reducing particle size of the cereal grain in swine diets not only improves efficiency of growth (as demonstrated in numerous KSU Swine Day Reports) but also decreases mix time needed for adequate blending and the likelihood of segregation during handling, storage, and delivery of diets to feeders.
Keywords: Swine; Mixing; Particle Size; Diet uniformity